96-week resistance analyses of the STaR study: rilpivirine/emtricitabine/tenofovir DF versus efavirenz/emtricitabine/tenofovir DF in antiretroviral-naive, HIV-1-infected subjects. Issue 1 (February 2015) - Porter, Danielle P.; Kulkarni, Rima; Fralich, Todd; Miller, Michael D.; White, Kirsten L.
Abstract : Background: STaR (GS-US-264-0110) was a 96-week phase 3b study evaluating the safety and efficacy of two single-tablet regimens, rilpivirine/emtricitabine/tenofovir DF (RPV/FTC/TDF) and efavirenz/emtricitabine/tenofovir DF (EFV/FTC/TDF) in treatment-naive, HIV-1-infected subjects. Methods: Genotypic analyses (population sequencing) of HIV-1 protease (PR) and reverse transcriptase (RT) were performed at screening; subjects with pre-existing resistance to study drugs were excluded. The protocol-defined resistance analysis population had genotypic/phenotypic analyses at failure and baseline for PR and RT. Results: Through week 96, the resistance analysis population included 24/394 subjects (6.1%) receiving RPV/FTC/TDF and 9/392 subjects (2.3%) receiving EFV/FTC/TDF. In the RPV/FTC/TDF arm, HIV-1 isolates from 21/394 subjects (5.3%) developed non-nucleoside reverse transcriptase inhibitor (NNRTI) and/or nucleoside reverse transcriptase inhibitor (NRTI) resistance mutations and 20/21 isolates had both NNRTI and NRTI genotypic and/or phenotypic resistance. In the EFV/FTC/TDF arm, isolates from 4/392 subjects (1.0%) developed NNRTI and/or NRTI resistance mutations. Resistance development after week 48 was infrequent (1.0% RPV/FTC/TDF; 0.3% EFV/FTC/TDF). When stratified by baseline HIV-1 RNA ≤ or >100 000 copies/ml, 9/260 (3.5%) versus 12/134 (9.0%) RPV/FTC/TDF-treated subjects and 3/250 (1.2%) versus 1/142 (0.7%) EFV/FTC/TDF-treated subjects developed resistant isolates, respectively. Pre-existing NRTI- and NNRTI-associated resistance mutations (not related to study drugs) did not impact treatment response to either regimen. Conclusions: Resistance development to RPV/FTC/TDF consisted of NNRTI and NRTI mutations and was more frequent than resistance development to EFV/FTC/TDF through week 96. Emergent resistance after week 48 was infrequent in both arms. Within the RPV/FTC/TDF arm, resistance development was more frequent in subjects with baseline HIV-1 RNA >100 000 copies/ml compared to baseline HIV-1 RNA ≤ 100 000 copies/ml.